Information literacy : key to an inclusive society : 4th European Conference, ECIL 2016, Prague, Czech Republic, October 10-13, 2016, Revised selected papers /: key to an inclusive society : 4th European Conference, ECIL 2016, Prague, Czech Republic, October 10-13, 2016, Revised selected papers. (2016) - Unknown
No abstract available